2016
DOI: 10.1007/s00540-016-2198-x
|View full text |Cite
|
Sign up to set email alerts
|

Intralipid in acute caffeine intoxication: a case report

Abstract: Caffeine is arguably the most widely used stimulant drug in the world. Here we describe a suicide attempt involving caffeine overdose whereby the patient's severe intoxication was successfully treated with the prompt infusion of Intralipid. A 19-year-old man was found in an agitated state at home by the volunteer emergency team about 1 h after the intentional ingestion of 40 g of caffeine (tablets). His consciousness decreased rapidly, followed quickly by seizures, and electrocardiographic monitoring showed ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…In cases of overdose, often intentional but sometimes undetermined and unintentional, at least 5 g or more (i.e., often around 10 g but up to 50 g) have been ingested leading to fatalities particularly if the individuals are not treated in time or at all. However, doses up to 50 g have also been treated successfully otherwise [ 29 , 30 ]. Some have indicated that after a dose of around 1 g, toxic symptoms begin to manifest, a dose of 2 g requires hospitalization, while higher doses (e.g., typically 5 g or more) could be lethal [ 27 , 28 , 31 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 4 more Smart Citations
“…In cases of overdose, often intentional but sometimes undetermined and unintentional, at least 5 g or more (i.e., often around 10 g but up to 50 g) have been ingested leading to fatalities particularly if the individuals are not treated in time or at all. However, doses up to 50 g have also been treated successfully otherwise [ 29 , 30 ]. Some have indicated that after a dose of around 1 g, toxic symptoms begin to manifest, a dose of 2 g requires hospitalization, while higher doses (e.g., typically 5 g or more) could be lethal [ 27 , 28 , 31 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The approach for management or treatment depends upon the particular patient’s symptoms, physical condition and the circumstances of their ingestion. For example, a mild overdose of 1 g with an individual displaying only mild side effects (e.g., restlessness, irritability, palpitations) might simply be monitored and perhaps administered a benzodiazepine whereas someone with a massive overdose might require numerous interventions [ 30 , 38 ]. Hemodialysis has also been effectively employed to reduce caffeine in plasma while decreasing morbidity in cases of intoxication [ 38 , 46 , 47 , 140 , 141 ].…”
Section: Management/treatment Strategiesmentioning
confidence: 99%
See 3 more Smart Citations